2019
DOI: 10.1002/anie.201901175
|View full text |Cite
|
Sign up to set email alerts
|

Inducing Enantioselectivity in a Dynamic Catalyst by Supramolecular Interlocking

Abstract: The design of an ew class of fluxional biphenyl bisphosphinite (BIBIPHOS) ligands decorated with amino acid-based diamide interaction sites is reported that undergo spontaneous desymmetrization. Hydrogenation of prochiral alkenes using Rh-BIBIPHOS results in enantiomeric ratios of up to 96:4 (R/S). This stereoconvergent behavior of the fluxional BIBIPHOS ligand is triggered by pronounced intermolecular interlocking of the recognition sites,l eading to the formation of as upramolecular assembly,w here the axial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 53 publications
(54 reference statements)
0
31
0
Order By: Relevance
“…The syntheses of the corresponding bisphosphinite ligands 9 a and 9 b has been reported by us in an earlier contribution. [19] Commercially available methyl vanillate 6 was dimerized to give compound 7. Subsequent ester cleavage and introduction of the selector units by two-fold amide formation yielded selector-modified biphenols 8 a,b, which were treated with chlorodiphenylphosphine in the final step of the reaction sequence to afford ligands 9 a,b.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The syntheses of the corresponding bisphosphinite ligands 9 a and 9 b has been reported by us in an earlier contribution. [19] Commercially available methyl vanillate 6 was dimerized to give compound 7. Subsequent ester cleavage and introduction of the selector units by two-fold amide formation yielded selector-modified biphenols 8 a,b, which were treated with chlorodiphenylphosphine in the final step of the reaction sequence to afford ligands 9 a,b.…”
Section: Resultsmentioning
confidence: 99%
“…We recently published preceding results of this phenomenon with a set of corresponding bisphosphinites, ligands 9 a and 9 b among them, and their respective biphenol precursors. [19] Herein, we expand by reporting a series of different phosphorous ligands with valine-and phenylalanine-based diamide selectors. Their self-assembling behavior was investigated, and the structure of the dimer was elucidated using singlecrystal X-ray structure analysis and NMR spectroscopy.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The investigated ligand design was found to trigger a process of spontaneous rotamer enrichment of the Ra isomer for all compounds (see Figure 7). [49][50][51][52] Comprehensive structural investigations revealed that the enrichment process is based on intermolecular interlocking of selector groups that entails the formation of highly-ordered ligand dimers. The point chirality of the amino acid-based selector units causes spatial confinement during this interaction, so that only the Ra rotamers can dimerize.…”
Section: R'mentioning
confidence: 99%
“…Earlier studies have shown that stereodynamic 3,3′‐methoxy‐2,2′‐biphenol‐based ligands with ( S )‐amino acid‐derived interaction sites (selectors) in the 5,5′‐position can be aligned by other ( S )‐amino acid‐derived diamides to induce the opposite stereo information during subsequent asymmetric hydrogenation reactions. Diamide selectors were found to interact in a highly enantioselective manner; however, overly efficient binding resulted in the formation of supramolecular ligand adducts and a concurrent loss of ligand's stereo dynamics . As a consequence, ligands with the same biphenyl core, decorated with ( S )‐phenylalanine‐derived amido ester groups, were to be investigated.…”
Section: Introductionmentioning
confidence: 99%